Reproductive performance of boer goats imported from Australia - Ching, Joveniah; Saad, Mohd Zamri (2010)
Assessment of reproductive parameters of Boer goats imported from Australia were made in a Boer Breeding Farm and a mixed-breed farm in Sabah. Data between 2008 and 2009 were sampled randomly and used to calculate pregnancy rate, prolificacy rate and kid mortality rate. The performance was compared with that of a mixed-breed goat farm. The pregnancy rate of imported Boer goats and the mixed-breed goats was 48 and 80% respectively. The difference was significant (P<0.05). Pregnancy rate was influenced by the nutrition, buck-to-doe ratio, health status of the breeding goats and environmental associate stress. There was significant difference (P<0.05) in the overall mean prolificacy rate between the two farms with the prolificacy rate in Boer goat at 145% while the mixed-breed goats at 113%. Prolificacy rate was related to the nutrition, age and parity of the dams. However, there was no significant (P > 0.05) difference in kid mortality rate between the farms. Kid mortality was attributed to inadequate nutrition, low birth weight, infectious diseases, helminthiasis, traumatic injury, poor mothering ability and lack of efficient management.